The potential for histone deacetylase (HDAC) inhibitors as cestocidal drugs - Vaca, Hugo Rolando (2021)
Background: Echinococcosis and cysticercosis are neglected tropical diseases caused by cestode parasites (family Taeniidae). Not only there is a small number of approved anthelmintics for the treatment of these cestodiases, but also some of them are not highly effective against larval stages, such that identifying novel drug targets and their associated compounds is critical. Histone deacetylase (HDAC) enzymes are validated drug targets in cancers and other diseases, and have been gaining relevance for developing new potential anti-parasitic treatments in the last years. Here, we present the anthelmintic profile for a panel of recently developed HDAC inhibitors against the model cestode Mesocestoides vogae (syn. M. corti).Methodology/principal findings: Phenotypic screening was performed on M. vogae by motility measurements and optical microscopic observations. Some HDAC inhibitors showed potent anthelmintic activities; three of them-entinostat, TH65, and TH92 -had pronounced anthelmintic effects, reducing parasite viability by ~100% at concentrations of ≤ 20 μM. These compounds were selected for further characterization and showed anthelmintic effects in the micromolar range and in a time- and dose-dependent manner. Moreover, these compounds induced major alterations on the morphology and ultrastructural features of M. vogae. The potencies of these compounds were higher than albendazole and the anthelmintic effects were irreversible. Additionally, we evaluated pairwise drug combinations of these HDAC inhibitors and albendazole. The results suggested a positive interaction in the anthelmintic effect for individual pairs of compounds. Due to the maximum dose approved for entinostat, adjustments in the dose regime and/or combinations with currently-used anthelmintic drugs are needed, and the selectivity of TH65 and TH92 towards parasite targets should be assessed.Conclusion, significance: The results presented here suggest that HDAC inhibitors represent novel and potent drug candidates against cestodes and pave the way to understanding the roles of HDACs in these parasites.